PENERAPAN MANAJEMENLAYANAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK INFORMATION TECHNOLOGY INFRASTRUCTURE LIBRARY V.3 (studi kasus STMIK Mardira Indonesia) - Jajat Sudrajat; Yucki Prihadi; Agus Iim Suryana (STMIK Mardira Indonesia, Bandung, 2019)
In the implementation of governance, information security factor is a very important aspect to be noticed, considering the performance of governance will be disrupted if the information as one of the main objects of governance experience information security issues concerning confidentiality, integrity, and availability. Because of this, it is necessary to have operational standard procedures to minimize the level of vulnerability. So we need an adequate information security management for system users to become safer and more comfortable.The operational standards are based on the information technology infrastructure library version 3 sub-service domain design service service catalog management and information security management to support adequate IT management and management.The result of this design is Standard Operating Procedure (SOP) for IT services. We expect this research can help STMIK Mardira Indonesia to improve its service capability and improve its security and role.Keywords: IT Services, ITIL V3, Service Design, Standard Operating Procedure DOI : http://doi.org/10.5281/zenodo.3625315